If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x + -1(-22) = -6 Multiply -1 * -22 x + 22 = -6 Reorder the terms: 22 + x = -6 Solving 22 + x = -6 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-22' to each side of the equation. 22 + -22 + x = -6 + -22 Combine like terms: 22 + -22 = 0 0 + x = -6 + -22 x = -6 + -22 Combine like terms: -6 + -22 = -28 x = -28 Simplifying x = -28
| -8.2p+7.2=p+267.56 | | -7x+3=-19 | | -3c+4=c+96 | | (24ab)(3)= | | a-17.72=1.6a+4 | | 5x-2c+1=15 | | 24overx=-10 | | -8x^3+5x^2-20x+250=0 | | -8q+8=q+311.3 | | 7.2=-3h | | -7-2x=-25 | | b+179.68=-3.7b+8.6 | | w+137=-2w+8 | | -p+8=p+44 | | 17=5k-02 | | 6.2y+7=2x-8.1 | | y+35.8=-y+5.8 | | x^2-1=15 | | 80-68= | | -29p-68=p+1432 | | 7ks-5=-19 | | 2(5x+4)=3(6x+2) | | 17x-8-13x=2(2x-5)+2 | | 19x+6=-881.3 | | 3x^2+5x-95=0 | | x-(-3)=25 | | 36-(4x+10)=4(x+2)+x | | c+42=-2c-27 | | 3g+5=89 | | 14-9x=-80-8x | | 160=10x-80 | | -13=-377 |